Assessment of genetic parameters of degradability in maize grains due to indentation scores (Scientia Agricola, 2011)
Maize (Zea mays L.) cultivars with dent grains present higher starch and dry matter ruminal degradability than those with flint grains. This study aimed to assess genetic parameters of degradability in maize grains of different textures and to verify whether there is an association between grain indentation score and ruminal dry matter (RDM) degradability. The evaluated progenies were obtained from the cross between the varieties Cristal (flint) and Cunha (dent), previously selected for grain hardness. Progenies were evaluated for an indentation score using a visual grading scale ranging from 1 (flint) to 5 (dent). To assess the RDM degradability, 5 g were cut into halves, weighed (five grams), stored in bags made of 100% "failet" cloth and incubated for 24 h in the rumen of three ruminally cannulated cows. There was genetic variability for RDM degradability and heritability was 46%, indicating the possibility of success using a selection. There was no association between indentation score and RDM degradability percentage; thus, visual evaluation not always reflects grain hardness per se since it indicates the pericarp aspect but not the endosperm constitution.